Evaluation of potential probionts from marine shellfish for black tiger shrimp Penaeus monodon (Fabricius, 1978) larviculture against vibriosis - Mohd Yaminudin, Nur Jasmin (2017)
Penaeid shrimp farming is one of the major contributors in annual world shrimp production. However, vibriosis has been one of the main diseases problems which often cause high mortality and decrease of production. Probiotics are now a leading new alternative in preventing vibriosis in Penaeus monodon culture. This study was carried out to discover new potential probiotics strain isolated from shellfish (shrimp and oyster) for tiger shrimp, Penaeus monodon larviculture culture. Total of 144 isolates of bacteria were successfully isolated from the intestine, hind gut and stomach of P. monodon and 136 isolates from shell, gills and digestive gland of oyster Crassostrea iredalei. In in vitro screening tests using series of plate assays, co-culture assay and pathogenicity test on TCBS agar, one isolate from shrimp and oysters each, showed potential as probiotics. Two potential probionts were identified as Bacillus megaterium (I24, from shrimp) and Exiguobacterium acetylicum (S66, from oyster) using 16S rRNA. Bacillus I24 able to excrete lipases, proteases and amylase meanwhile Exiguobacterium S66 was positive in excreting amylase and lipases only. Both potential probionts were able to produce biofilm, slightly reduced haemolysis and did not showed anti-quorum sensing properties. A preliminary in vivo assay for the two potential probionts were carried out on Artemia salina challenged with Vibrio harveyi and Vibrio alginolyticus. Results demonstrated a significant survival of Artemia after treated with probiont Bacillus I24 at 108 CFU mL-1 and challenged with V. harveyi (73.33±0.88%) and V. alginolyticus (98.33±0.33%) compared to the control Artemia with pathogen only (V. harveyi 23.33±0.23%, V. alginolyticus 36.67±0.33%). Moreover, Artemia treated with Exiguobacterium S66, at concentration 108 CFU mL-1 also showed high survival (95±0.58%) after challenged with V. harveyi (V. harveyi only 23.33±0.33%). There was a significant reduction of vibrios in Artemia treated with Bacillus I24 and Exiguobacterium S66 at 108 CFU mL-1 compared to the control group. Similar results were observed in in vivo test by using P. monodon postlarvae (PL) as a host. Postlarvae treated with Bacillus I24 at 106 CFU mL-1 had significant high survival after challenged with the pathogens V. harveyi (88.33±1.45%) and V. alginolyticus (78.33±1.33%) at 106 CFU mL-1. Meanwhile, PL treated with Exiguobacterium S66 at concentration 106 CFU mL-1 showed significant high survivals (93.33±0.88%) after challenged with V. harveyi. Vibrios counts were significantly lower in PL and culture water treated with Bacillus I24 and Exiguobacterium S66 at the end of challenged assay. Specific growth rate in terms of weight and length were shown to be higher in larvae treated with both potential probionts compared to control groups with vibrios only. Results indicate PL treated with potential probionts had faster growth rate. This research suggests that Bacillus I24 and Exiguobacterium S66 have potential to be commercialized as probiotics for aquaculture industry specifically for shrimp culture.